Synthesis, Characterization and Anti-Cancer Studies of Curcumin Diketimines-Heteropolyacid Composites - Samannan, Bharath; Selvam, Jothi; Thavasikani, Jeyabalan (Asian Journal of Chemistry, 2020)
A novel composite of curcumin diketimine (CDK)-heteropolyacid (where HPA = vanadium doped Keggin anion and CDK = curcumin-benzoguanamine) had been synthesized. The hybrid composites were investigated by analytical methods such as elemental analysis, FT-IR, 13C NMR, SEM, EDS, XRD, DSC-TGA, ESR spectral studies and biological activities. Encapsulated hybrid composite also studied (in vitro) against MCF-7 cancer cell lines. ESR results showed that the presence of (V4+) ion nitrogen ligation in the composite. 13C NMR of CDK ligand value of 183.37 and 55.06 ppm corresponds to (2=N) and (O-CH3) may be due to the composites. The morphology of molybdovanadate (HPA) showed a structure of self-assembled round shape of a diameter around 1 μm.